40th Fluid Dynamics Conference and Exhibit 2010
DOI: 10.2514/6.2010-4863
|View full text |Cite
|
Sign up to set email alerts
|

Computation of the Flow of a Dual-Stream Jet with External Solid and Perforated Wedge Deflectors for Noise Reduction

Abstract: We present a methodology for the computation of flow fields involving complex perforated surfaces in propulsion applications. Of particular interest is the treatment of perforated flaps used as wedge-shaped fan flow deflectors for reducing jet noise of a supersonic turbofan engine. A three-dimensional Reynolds-Averaged Navier-Stokes solver is used to compute the flow field of the external jet plume with solid and perforated deflector flaps, the latter with 50% porosity. Flow computation for perforated flaps pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…3 During noise-sensitive segments of the flight, the flaps could be deployed and the vane deflectors actuated. Computational predictions of specific-thrust loss for the entire engine (including the core stream) are 0.39% from the optimal vane arrangement and 0.53% from the wedge, 10 for a total thrust loss of 0.92%. During portions of the flight when noise reduction is unnecessary, such as cruise, the wedge flaps could be retracted and the vanes positioned at α = 0 o .…”
Section: Discussionmentioning
confidence: 99%
“…3 During noise-sensitive segments of the flight, the flaps could be deployed and the vane deflectors actuated. Computational predictions of specific-thrust loss for the entire engine (including the core stream) are 0.39% from the optimal vane arrangement and 0.53% from the wedge, 10 for a total thrust loss of 0.92%. During portions of the flight when noise reduction is unnecessary, such as cruise, the wedge flaps could be retracted and the vanes positioned at α = 0 o .…”
Section: Discussionmentioning
confidence: 99%
“…5. Past computations on solid FFD wedges have shown that the flow angularity at the measurement locations was typically less than 20 deg [16]. At these shallow angles, the error in the pitot measurement due to misalignment is less than 1% [18].…”
Section: B Mean Wake Surveysmentioning
confidence: 99%
“…To facilitate the interpretation of the results of this study, it is useful to have an overall understanding of the aerodynamics of the FFD wedge, focusing initially on the solid case. These observations are based on past experiments and computations of the FFD wedge flow [15,16], and the experiments of Von Tanner on the drag of 2-D wedge cylinders [17]. We note that the FFD wedge acts on a flow bounded by a free surface: the shear layer between the fan stream and the ambient.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…For a porous plate normal to a flow, the inertial resistance coefficient is primarily a function of porosity. 10 As a first approximation, the inertial resistance coefficient was obtained by calibrating the model against experimental measurements of drag coefficient for a perforated plate inclined normal to a freestream. 11 The coefficient of drag is plotted versus porosity in Fig.…”
Section: B Simulation Using Body Force Termmentioning
confidence: 99%